Estratégias sócio-interacionais na construção da notícia jornalística - Paula, Deborah Gomes de (2008)
This Dissertation is situated on the Critical Analysis of the Discourse with a social-cognitive shed. It has as a general objective to contribute for the criticals studies of brazilian journalistic discourse. It has as specifics objectives: 1. to examine the construction of headlines; 2. to analyse the construction of news on reduced-texts (headlines, thin-lines and leads); 3. to verify how an news can be modify an scandal; 4. to present an perspective for a reading of journalistics texts multimodals. The main goal of research to examine reduced-texts (headlines, thin-lines and leads). It has an inter-relation between analytics categories Society, Cognition and Discourse because each one is defined by other. Has by hypothesis that the strategies of social-interactions guarantee the discourse interaction between the newspaper and his readers. The material of analysis was chosen from paulistanos journals O Estado de S. Paulo, Folha de S.Paulo, Jornal da Tarde, Diário de S.Paulo e Agora São Paulo to select the reduced-texts on First Page and on differents news items. The analysis procedure was theorical-analytic, to the parts selected and inter-related. The obtained results indicate that:: 1) the strategies presents a social variable in relation the socials cognitions by the interactions strategies for construction of headlines: by information, opinion and seduction; 2) the differents constructions of news analysed by sequencial cohesion of reduced-texts that permits the progression of news to built the journalistics happened by ideology of newspaper; 3) the news modified on a scandal when the private on character´s life in the narrative way became public, by revelation; 4) the perspective by journalistics texts multimodals presents a inter-relation between the selection of texts elements multimodals and the cultural from social groups of readers. In conclusion, the strategies social-interactions change by cognitions mark of readers group constructed on and by Discourse